The Study of Artificial Hills in the Territory of Bukhara Region on the Example of Jondor District (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The study of artificial hills in the territory of Uzbekistan, the history of their origin and the meaning of their naming, drawing up a map of their location, creating a survey of objects and creating a tourist route on them.